Comparison of single- and triple-port VATS for lung cancer: A meta-analysis - Gao Yunfei (De Gruyter, 2021)
To compare the perioperative parameters between single- and triple-port video-assisted thoracoscopic surgery (VATS) lobectomy in the treatment of lung cancer.